Isolation and Identification of Antibacterial Compound from Punica granatum L. Fruit Peels Grown in Iraq - Mohammed Taha Mahmood; Muthanna J. Mohammed; Firas Abbas Al-Bayati (College of Education for Pure Sciences, 2010)
Abstract The aim of this study was to isolate and identify the substance responsible for the pharmacological activities of Punica granatum L. fruit peels. Tannic acid (ellagitannins, gallotannins) was isolated from pomegranate fruit husk and detected on Thin layer chromatography TLC plates in comparison with standard tannic acid that, served as a positive control. Moreover, infrared FTIR spectrometer and High Performance Liquid Chromatography HPLC analysis were used to confirm the purity and characterization of tannic acid. The isolated material was investigated for its antibacterial activity against six different pathogenic bacteria. The Gram-positive bacteria were; Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes; and Gram-negative bacteria included; Brucella melitensis, Klebsiella pneumoniae and Pseudomonas aeruginosa. Tannic acid at different concentrations (50.0, 25.0, 12.5, 6.2 mg/ml) was active against all tested bacteria and the highest inhibitory effect was observed against K. pneumoniae (zone of inhibition: 22.6 mm) using the disc diffusion method. The minimal inhibitory concentration MIC for tannic acid was determined using a broth microdilution method in 96 multi-well microtiter plates. MIC values ranged from 31.2-250.0 μg/ml, and the most promising result was observed against K. pneumoniae.